2017
DOI: 10.1002/open.201700024
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of G‐Rich Oligonucleotides Incorporating a 3′–3′ Inversion of Polarity Site: A New Route Towards G‐Wire DNA Nanostructures

Abstract: Obtaining DNA nanostructures with potential applications in drug discovery, diagnostics, and electronics in a simple and affordable way represents one of the hottest topics in nanotechnological and medical sciences. Herein, we report a novel strategy to obtain structurally homogeneous DNA G‐wire nanostructures of known length, starting from the short unmodified G‐rich oligonucleotide d(5′‐CGGT‐3′–3′‐GGC‐5′) (1) incorporating a 3’–3′ inversion of polarity site. The reported approach allowed us to obtain long G‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…Both GQs showed remarkable antiproliferative activity against cancer cell lines [ 211 ]. Oliviero et al [ 212 ] published on polarity site inversion GQs with the aim of obtaining structurally homogenous DNA G-wire nanostructures, using 5′-CGGT-3′-3′-GGC-5′ sequences. An NMR study performed by Šket et al on the tetramolecular GQs formed by TG 3 T and its analogs containing a 5′-5′ or 3′-3′ inversion of polarity site, namely, the 3′TG5′-5′G 2 T3′, 3′T5′-5′G 3 T3′, and the 5′TG3′-3′G 2 T5′, revealed that the parallel GQs had distinct cation-binding preferences [ 213 ].…”
Section: Stabilization or Destabilization Of A Gq By The Same Syntmentioning
confidence: 99%
“…Both GQs showed remarkable antiproliferative activity against cancer cell lines [ 211 ]. Oliviero et al [ 212 ] published on polarity site inversion GQs with the aim of obtaining structurally homogenous DNA G-wire nanostructures, using 5′-CGGT-3′-3′-GGC-5′ sequences. An NMR study performed by Šket et al on the tetramolecular GQs formed by TG 3 T and its analogs containing a 5′-5′ or 3′-3′ inversion of polarity site, namely, the 3′TG5′-5′G 2 T3′, 3′T5′-5′G 3 T3′, and the 5′TG3′-3′G 2 T5′, revealed that the parallel GQs had distinct cation-binding preferences [ 213 ].…”
Section: Stabilization or Destabilization Of A Gq By The Same Syntmentioning
confidence: 99%
“…The classification of higher-order G4 structures has been outlined in a recent work by Oliviero et al. ( 10 ). According to this classification, the two ‘marginal’ types of multimers are interlocked G-wires, which are composed of mutually slipped G-rich strands, and stacks of G4s, which are held together by interquadruplex pi–pi stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at further confirming the binding of α,ε-PLL with the two G4 models and also at investigating the effect of the addition of α,ε-PLL on the molecularity of Tel22 and Pu22 G4s, we used the HPLC size exclusion chromatography (HPLC-SEC) technique. In other papers, in fact, we and others demonstrated that the HPLC-SEC could be successfully exploited to assess the molecularity and conformational changes of DNA G4s [43][44][45]. Accordingly, we recorded the HPLC-SEC profiles of Tel22 and Pu22 G4s before and 96 h after their incubation with α,ε-PLL ( Figure 8).…”
Section: Resultsmentioning
confidence: 94%